A highly efficient rGO grafted MoS2 nanocomposite for dye adsorption and electrochemical detection of hydroquinone in wastewater. (26th October 2022) - Verma, Sakshi; Pandey, Chandra Mouli; Kumar, D.
Abstract : Scheme depicting the synthesis and the fabrication of rGO–MoS2 nanocomposite-based enzymatic biosensor for estimation of hydroquinone. Abstract : A reduced graphene oxide–molybdenum disulfide (rGO–MoS2 ) nanocomposite has been synthesized using a hydrothermal method, which has been further used to remove water pollutants and for electrochemical detection of polyphenol compounds. The synthesized nanocomposite showed excellent adsorption efficiency and can effectively adsorb methylene blue dye (97%) from an aqueous solution using minimal adsorbent in a few minutes. A biosensing electrode has been fabricated by depositing the synthesized nanocomposite electrophoretically onto an indium tin oxide-coated glass substrate, followed by the covalent immobilization of the laccase (Lac) enzyme. The Lac/rGO–MoS2 bioelectrode showed a high sensitivity (0.027 μA μM −1 cm −2 ), a wide detection range (1–100 μM), and a low detection limit of 0.1 μM for hydroquinone (Hq) detection in real water (tap and river) samples with excellent recovery rate. Moreover, the proposed biosensor was found to be stable, reusable, and can potentially be used as an efficient platform for the detection of phenolic pollutants.